Tráfico y consumo de sustancia estupefaciente y psicotrópicas sujetas a fiscalización en los adolescentes en Guayaquil - Coello Icaza, Carlos Mauricio (2016)
Adolescents whose average age between 12 and 17 years in a high percentage of students from different educational units of Guayaquil and from different social strata are involved increasingly common in traffic and consumption of narcotic drugs and psychotropic substances under control, reaching the point of generating a social warning. This has caused a deep analysis whose field of research has focused on the prospect with lawyers in cases of consumption and trafficking of drugs in adolescents, with the object of an analysis on possible causes of this problem type criminological partner, considering that the educational measures established in Art. 385 of the Penal code in force Integral conjunction with the code of childhood and Adolescence in the art. 385 turn out to be ineffective in controlling and eradicating trafficking and consumption of narcotic drugs and psychotropic substances under control by young people, called by the same law as Juvenile Offenders and therefore qualified also criminally responsible….